2015
DOI: 10.4236/msa.2015.68078
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Steel Pipelines Transporting Hydrocarbon Condensed Products, Obtained from a High Pressure Separator System: A Failure Analysis Study

Abstract: In this paper, the corrosion of steel pipelines transporting hydrocarbon condensed products was studied. Different activities of sampling and analysis were carried out to diagnose the failure causes and to establish a control system for the corrosion problem. The combination of three types of corrosion, including erosion corrosion, galvanic corrosion and microbiologically induced corrosion, was synthetically considered. A serial of experiments were designed to research those types of corrosion. This type of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…- Corrosion of carbon steel used in the petroleum industry for pipelines or tanks is mainly caused by the presence of water, corrosive gases (H 2 S, CO 2 and O 2 ), chlorides and microorganisms. The most common form of corrosion occurs when carbon steel comes in contact with an aqueous solution, for instance, when CO 2 is dissolved in water, corrosive carbonic acid is formed [43][44][45][46][47][48][49]. Sulfolane in the presence of water and air also forms an aqueous solution of sulphurous acid [24][25][26].…”
Section: Corrosion Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…- Corrosion of carbon steel used in the petroleum industry for pipelines or tanks is mainly caused by the presence of water, corrosive gases (H 2 S, CO 2 and O 2 ), chlorides and microorganisms. The most common form of corrosion occurs when carbon steel comes in contact with an aqueous solution, for instance, when CO 2 is dissolved in water, corrosive carbonic acid is formed [43][44][45][46][47][48][49]. Sulfolane in the presence of water and air also forms an aqueous solution of sulphurous acid [24][25][26].…”
Section: Corrosion Resistancementioning
confidence: 99%
“…For example, an iron carbonate protective layer can be formed on the surface of carbon steel and low-alloy steels (to 9 wt.% Cr) used in the petroleum industry. However, note that fluid movement or the temperature often break down the FeCO 3 layer accelerating corrosion process [46][47][48][49]. It was found that for the water concentration in the range from 1 to 4 vol.%, a protective layer stabilizes the corrosion rate of AISI 1010 steel in sulfolane at a certain level.…”
Section: Corrosion Resistancementioning
confidence: 99%